A new Algorithm to Solve Multi-Objective Optimization Problem Based on Decomposition Property - Hmood, Rajwan; T.Abbas, Iraq; AlSattar, H. A. (Sulaimani Journal for Pure and Applied Sciences, 2020)
MOBATD is a multi-target bat calculation that fuses the strength idea with the decay approach is proposed as another calculation. While decay improves the multi-target issue (MOP) by changing it as a lot of Tchebycheff Approach, taking care of these issues all the while, inside the BAT structure, may prompt untimely assembly in light of the pioneer determination process which utilizes the Tchebycheff Approach as a model. Predominance assumes a significant job in building the pioneers document permitting the chose pioneers to cover less thick areas staying away from neighborhood optima and bringing about a progressively differing approximated Pareto front. Results from 12 standard MOPs show MOBATD outflanks two cutting edge decay based transformative techniques.
Keywords: Multi-objective problem; Multi-Objective Bat Algorithm; Decomposition Property; Performance Measure